2009
DOI: 10.1007/s00464-009-0449-8
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative bariatric screening and treatment of Helicobacter pylori

Abstract: Preoperative H. pylori screening should continue, especially in geographically high-prevalence areas, as data suggest that the incidence of viscus perforation may be reduced with preoperative treatment if indicated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(22 citation statements)
references
References 6 publications
0
20
0
2
Order By: Relevance
“…Screening of H. pylori could be performed without endoscopy by noninvasive methods and eradication is recommended for all positive patients, especially in geographically highprevalence areas, as data suggest that the incidence of viscus perforation may be reduced with preoperative treatment. [20].…”
Section: Discussionmentioning
confidence: 95%
“…Screening of H. pylori could be performed without endoscopy by noninvasive methods and eradication is recommended for all positive patients, especially in geographically highprevalence areas, as data suggest that the incidence of viscus perforation may be reduced with preoperative treatment. [20].…”
Section: Discussionmentioning
confidence: 95%
“…12 Other studies looking at complications following gastric bypass surgery in patients with H. pylori infection also suggest some relation between postoperative complications and the presence of H. pylori. 9,13 Although this may imply a benefit to preoperative screening and treatment, there are also conflicting studies. One study found no association with H. pylori seropositivity and postoperative ulcer formation after gastric bypass.…”
Section: Discussionmentioning
confidence: 99%
“…However, the prevalence of H. pylori infection in morbidly obese patients and its effect on ulcer progression or the response to eradication treatments is unresolved [13][14][15][16][17][18]. Furthermore, it is also unclear whether the detection and eradication of H. pylori prior to bariatric surgery can reduce the risk of postoperative peptic ulcer disease [19,20]. These dilemmas are not surprising when we consider the variation in H. pylori prevalence according to geographical region, which is influenced by socio-economic environments and eating habits.…”
Section: Discussionmentioning
confidence: 99%